Dynamics and Implications of Distress Organizing - Kahn, William A. (Academy of Management Journal, 2019)
This study offers a theory-generating examination of the social construction processes through which members regularly exposed to psychological distress navigate paradoxical demands to both extend and protect the self in their work with others. A qualitative study of a child welfare agency found that members organized themselves to avoid the conscious experience of psychological distress. Distress organizing involved, first, the use of collective avoidance mechanisms that constrained the time, space, and impetus for members to experience the distress of their work; and, second, patterns of interpersonal avoidance that prevented relationships in which such experiencing could occur. The mutually reinforcing, cumulative effect of distress organizing sharply reduced members’ emotional availability to clients and coworkers, which manifested as largely dispassionate responses to others’ distress. Dispassionate responding led to emotional isolation and emotional exhaustion, with which members coped by further avoidance of others. Distress organizing thus amplified rather than ameliorated distress. Amplification processes were temporarily suspended when agency members momentarily created conditions for providing and receiving compassion. These findings contribute to theory about social contexts of psychological distress in organizations, the alleviation of such distress, and the bases of organizing processes.